Memory and popular film - Grainge, Paul, 1972- (Inside popular film., 2003)
"Memory and Popular Film" uses memory as a specific framework for the cultural study of film. Taking Hollywood as its focus, the text provides a sustained, interdisciplinary perspective on memory and film, from early cinema to the present.